Peningkatan Kompetensi Tutor Lembaga Non-Formal melalui Pendekatan Literature-Based Language Learning di Bimbel Merauke Cerdas: Pengabdian - Arin Mantara Anggawirya; Abdurrahman Shaleh Reliubun; Yuni Ratna Purwaningsih; Rosalia Floriani; Evelin Giovani; Nurul Istiqomah; Survey Sijabat (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service program aimed to enhance the competence of tutors in non-formal educational institutions in implementing the Literature-Based Learning (LBL) approach in teaching. The two-day training was conducted at Bimbel Merauke Cerdas, South Papua, involving 12 participating tutors. The training employed a combination of conceptual material delivery and hands-on practice, designed to equip participants with an understanding of the theoretical foundations of LBL, its connection to Communicative Language Teaching (CLT), Vygotsky’s sociocultural theory, and Reader-Response theory. The results showed a significant increase in average scores: cognitive (from 3.06 to 4.00), practical skills (from 2.98 to 3.79), and perception (from 3.07 to 3.98). These findings indicate the training's success in enhancing conceptual understanding, instructional design skills, and participants’ positive attitudes toward LBL implementation. In conclusion, the training effectively strengthened the tutors’ theoretical knowledge, practical competencies, and reflective abilities in adopting literature as an integral part of the learning process.